(untitled) (Third Sector Social Economic Review, 2019)
The purpose of this study is; individuals living in Turkey is to determine the level of financial literacy. For this purpose, a survey was applied investors who buy and sell stocks in Borsa Istanbul, public and private sector employees, self-employed persons, retirees and students and to 2300 individuals on 25 different city. Turkey in general financial literacy level of success of the study was determined to be 52.49%. Moreover, it was determined that financial literacy achievement levels are much higher than investors who buy and sell stocks. The financial literacy level of participants varies according to demographic variables such as gender, age, marital status, income, occupation, education level.